2019
DOI: 10.20945/2359-3997000000104
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of dehydroepiandrosterone sulfate are associated with the risk of developing cardiac autonomic dysfunction in elderly subjects

Abstract: Objective: To assess the relationships between serum dehydroepiandrosterone sulfate (DHEA-S) levels and heart rate variability (HRV) among different age groups. Subjects and methods: Fortyfive healthy men were divided into 3 groups: young age (YA; 20-39 yrs; n = 15), middle age (MA; 40-59 yrs; n = 15) and old age (OA; ≥ 60 yrs; n = 15). Hemodynamic parameters, linear analyses of HRV and concentrations of cortisol and DHEA-S were measured at rest. Results: The OA group presented a higher resting heart rate (84.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Available data for the associations between salivary DHEA and cardiac autonomic regulation are very scarce but show the same trend of a positive correlation between HRV measures and DHEA or DHEA-S levels (17)(18)(19). Although the exact mechanisms of DHEA(S) effects on sympathovagal balance are unclear, it is hypothesized that the existence of cardiac DHEA(S) receptors and the regulatory effects of DHEA(S) on sympathetic adrenal activity may serve as an essential linkage between increased HRV and higher DHEA(S) levels in blood serum or saliva samples (17,19). Previous research suggested that administration of DHEA in young adult males has been related to diminished activation of the amygdala and hippocampus (20).…”
Section: Discussionmentioning
confidence: 99%
“…Available data for the associations between salivary DHEA and cardiac autonomic regulation are very scarce but show the same trend of a positive correlation between HRV measures and DHEA or DHEA-S levels (17)(18)(19). Although the exact mechanisms of DHEA(S) effects on sympathovagal balance are unclear, it is hypothesized that the existence of cardiac DHEA(S) receptors and the regulatory effects of DHEA(S) on sympathetic adrenal activity may serve as an essential linkage between increased HRV and higher DHEA(S) levels in blood serum or saliva samples (17,19). Previous research suggested that administration of DHEA in young adult males has been related to diminished activation of the amygdala and hippocampus (20).…”
Section: Discussionmentioning
confidence: 99%